The girl of his dreams [large type] - Leon, Donna (Leon, Donna. Commissario Guido Brunetti mystery., 2008)
One cold and rainy morning, the body of a gypsy girl is found floating in a canal. Brunetti suspects she fell off a nearby roof while fleeing an apartment she had robbed--but something about the case continues to haunt him.